OPTIMALISASI PENDIDIKAN KARAKTER SEBAGAI SARANA PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK - Bashirotul Hidayah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Education is one of the factors that play an important role in order to be able to print the nation's next generation of quality and can make a positive contribution to the life of the nation because without a good education, the next generation of the nation will also not be of quality. best for their students. Character Education is considered to have been proven to be effectively able to increase the motivation of students in achieving learning achievement. Character education is education that is deliberately sought to build people to understand, care about, and act on the basis of ethical values.